MULTIPLE MYELOMA PATIENTS UNDERGOING CARFILZOMIB: VALIDATION OF A MANAGEMENT PROTOCOL FOR CARDIOVASCULAR RISK ASSESSMENT AND A NEW SCORE FOR EVENTS PREDICTION. (April 2021) - Astarita, Anna; Mingrone, Giulia; Airale, Lorenzo; Cesareo, Marco; Vallelonga, Fabrizio; Bruno, Giulia; Leone, Dario; Giordana, Carlo; Rabbia, Franco; Salvini, Marco; Gay, Francesca; Bringhen, Sara; et al.
Abstract : Objective: Cardiovascular adverse events (CVAEs) are closely related to Carfilzomib (CFZ) therapy in multiple myeloma (MM), however no validated management protocols are available. This perspective study investigated the effectiveness of the European Myeloma Network protocol (EMN) in cardiovascular risk assessment. A risk score to predict CVAEs was developed and the type and incidence of CVAEs were assessed. Design and method: 116 MM patients scheduled for CFZ underwent a baseline evaluation including office and out-of-office blood pressure measurements, ECG, echocardiography (included GLS) and arterial stiffness estimation. The repeated evaluations every 3–6 months allow CVAEs detection. Results: During a median of 10.8 months of follow-up, 62 patients (53.4%) experienced one or more CVAEs: 17 (14.7%) had major CVEAs (41.2% arrhythmias, 23.5% acute ischemic cardiopathy as most frequent) and 45 (38.7%) had hypertensive CVAEs. 51.9% of CVAEs occurred within the first 3 months, with 30.9% grade 3 or greater in severity. At baseline the prevalence of uncontrolled blood pressure values (51.7%) and of subclinical organ damage, were substantial. Five baseline parameters have proved to be independent predictors for CVAEs: higher office systolic blood pressure (p = 0.003), higher 24-hours blood pressure variability (p = 0.004), left ventricular hypertrophy (p = 0.021), higher pulse wave velocity value (p = 0.002) and global longitudinal strain impairment (p = 0.033). The resulting CVAEs risk score allows to define a low- and high-risk group, obtaining a sensibility of 94% in detecting CVAEs in the high-risk (AUC 0.76). Figure. No caption available. Conclusions: CFZ therapy is closely linked to CVAEs developing in MM patients. The application of the EMN protocol and the use of the CVAEs risk score might be useful to correctly estimate the cardiovascular risk profile and to identify the higher risk patients, enabling risk mitigation strategies.